Feline Notoedric Mange: Therapeutic Management and Zoonotic Implications - Chandrasekha, M; Vidhya, M Sree; Arunkuma, S; Sweta,; Vijay, A; Ranjithkumar, M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Three month old, five kittens were brought to the Emergency Critical Care Unit of Madras Veterinary College, Chennai, with the history of  intense pruritus in the animals. On physical examination, alopecia and hyperkeratotic crusts were seen on the animal body, particularly  on the pinna, head and legs. Pinna pedal reflex was also observed to be positive for animal. Skin scrapings were collected from the tip  of the ear of affected kittens. The collected material examined by using liquid paraffin under the low power microscope revealed the  presence of Notoedrus cati mites, indicating that cats were affected with notoedric mange. The owner also reported instances of itching  among family members in the recent past. Upon examination, lesions were observed even on the owner’s hands, suggesting a potential  mange infestation. There were earlier reports about zoonotic risk of notoedric mange from India.
Keywords: Excoriation; Microscopy; Notoedric mange; , Pinna-pedal reflex; Pruritus; Zoonoses.